Oxygen plasma cleaning of copper for photocathode applications: A MEIS and XPS study. (November 2022) - Noakes, T.C.Q.; Valizadeh, R.; Hannah, A.N.; Jones, L.B.; Militsyn, B.L.; Mistry, S.; Cropper, M.D.; Rossall, A.; Van den Berg, J.A.
Abstract: MEIS and XPS studies have been conducted for a range of oxygen plasma treated copper samples (and one treated with Ar plasma), as part of a study of the preparation of photocathode surfaces. This procedure was seen to remove hydrocarbon contamination, but left an oxide film whose thickness depended on the treatment conditions used. The film thickness was seen to increase with longer treatment time and higher RF power levels with behaviour characteristic of a diffusion limited process. Annealing led to a removal of the oxide layer by diffusion of oxygen into the bulk of the samples. This indicates that where the oxide layer is sufficiently thin, it should be possible to produce a surface with low enough oxygen content to have adequate conductivity and high enough surface escape probability to allow photoemission at UV wavelengths. Ar plasma treatment was seen to result in a very thin oxide film which could satisfy these requirements and thus might be preferable. Data from single crystal copper samples showed similar total oxygen content for all the surfaces analysed. Highlights: MEIS and XPS have been used to study O (and to a lesser extent Ar) plasma cleaned samples of copper. Data indicate diffusion limited oxidation of the surface with oxide film thickness dependent on treatment time and power level. The resultant oxide film is O rich being CuO2, Cu(OH)2 or CuO with significant adsorbed O. Annealing oxidised samples causes the O to diffuse into the bulk leaving an essentially pure Cu in the surface region. Mild O plasma cleaning (or Ar plasma) followed by annealing is an effective treatment for photocathode applications.